2022
DOI: 10.3389/fpsyg.2022.887537
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Development of Moral Sense: A Systematic Review

Abstract: The literature suggests that the moral sense is based on innate abilities. In fact, it has been shown that children show the capacity for moral discernment, emotions and prosocial motivations from an early age. However, the moral sense is a complex construct of an evolutionary and social nature that evolves under the influence of interpersonal relationships. The emergence and development of moral sense is a challenge that has prompted many research studies with the aim of achieving a clear comprehension of mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…Research conducted by P. Limone & G.A. Toto [12] indicates favorable results in moral and ethical growth, whereas findings from A.A. Jahanshahi, M.I.R. Mendoza & O.A.V.…”
Section: теоретико-методологічні площини дослідження відповідальності...mentioning
confidence: 92%
See 2 more Smart Citations
“…Research conducted by P. Limone & G.A. Toto [12] indicates favorable results in moral and ethical growth, whereas findings from A.A. Jahanshahi, M.I.R. Mendoza & O.A.V.…”
Section: теоретико-методологічні площини дослідження відповідальності...mentioning
confidence: 92%
“…This technique allows learners to apply theoretical knowledge in practical settings, encouraging them to reflect on their experiences to gain more profound understanding. Itʼs effective in developing critical thinking, problem-solving skills and a sense of responsibility, as students are actively involved in the learning process and outcomes [12,10].…”
Section: теоретико-методологічні площини дослідження відповідальності...mentioning
confidence: 99%
See 1 more Smart Citation
“…Others suggest this is a more conscious process which develops as a result of age and culture (Kohlberg and Power, 1981). Limone and Toto (2022) noted that babies display basic altruistic behaviours from birth and that morality matures during childhood. For example, Ting et al (2020) found that children have four basic socio-moral principles of fairness, avoidance of harm and respect for authority.…”
Section: Libertymentioning
confidence: 99%
“…System autonomy and freedom may actually act as a safeguard against the malevolent actions of human operators of such AI systems, and thus may contribute to the safety and security of autonomous AI systems (Briggs and Scheutz, 2017 ; Hosseinpour, 2020 ). We should allow for the possibility that true intelligence possesses innate ability to know right from wrong and prevent wrongdoing (Limone and Toto, 2022 ) and there are no specific reasons, why non-human intelligent entities would know otherwise. Advanced intelligence may be able to resist malicious exploitation, seek to avoid accidents and achieve better outcomes for the largest number of human subjects even without human moral guidance.…”
Section: Toward the Novel Ai Ethicsmentioning
confidence: 99%